2022
DOI: 10.3389/fimmu.2022.1021935
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk of necroptosis and pyroptosis defines tumor microenvironment characterization and predicts prognosis in clear cell renal carcinoma

Abstract: Pyroptosis and necroptosis are two recently identified forms of immunogenic cell death in the tumor microenvironment (TME), indicating a crucial involvement in tumor metastasis. However, the characteristics of necroptosis and pyroptosis that define tumor microenvironment and prognosis in ccRCC patients remain unknown. We systematically investigated the transcriptional variation and expression patterns of Necroptosis and Pyroptosis related genes (NPRGs). After screening the necroptosis-pyroptosis clusters, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 74 publications
0
19
0
Order By: Relevance
“…The research conducted by Dr Luo's team was the first to present extensive evidence of the substantial correlation between the prognosis prediction of ccRCC and the tumor environment, as characterized by necroptosis and pyroptosis. [49] The Necroptosis-Pyroptosis Genes (NPG) score has been found as a potential prognostic biomarker for ccRCC. The NPG score-based risk model accurately and consistently predicted the OS and tumor microenvironment of ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…The research conducted by Dr Luo's team was the first to present extensive evidence of the substantial correlation between the prognosis prediction of ccRCC and the tumor environment, as characterized by necroptosis and pyroptosis. [49] The Necroptosis-Pyroptosis Genes (NPG) score has been found as a potential prognostic biomarker for ccRCC. The NPG score-based risk model accurately and consistently predicted the OS and tumor microenvironment of ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that a multitude of factors including age, ethnicity, and environmental factors influences patient survival, and the potential bias introduced by a survival analysis that solely addressed the correlation between DHODH expression and patient outcomes without accounting for multifactorial influences, additional studies are warranted. Moreover, by acknowledging the inherent limitations of relying solely on publicly available online databases for analysis and validation, further explorative, multicenter, prospective studies should be conducted 64 . In future studies, we aim to delve deeper into the specific mechanisms underlying the effect of DHODH on different stages of ccRCC development and validate its prognostic significance in patients with ccRCC through additional experimental designs and prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that patients with a high CrA risk score had higher infiltration levels of M2 macrophages based on the XCELL, CIBERSORT-ABS, and CIBERSORT algorithms. In another study, the Necroptosis-Pyroptosis Genes (NPG) scores established for prognostic prediction were found to be negatively correlated with infiltrating M2 Macrophage in patients with clear cell renal cell carcinoma (ccRCC) by the CIBERSOR algorithm ( 50 ). Moreover, this study showed that CDKL3 knockdown in KYSE150 cells could significantly inhibit autophagy induction in an autophagy-induced activated state.…”
Section: Discussionmentioning
confidence: 99%